Indonesia : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2010)
Indonesia has improved fiscal transparency; tax legislation has been substantially revised; tax administration is improving; legal and administrative measures have been adopted to improve public sector governance; and important steps have been taken to rationalize government banking arrangements. However, much remains to be done to improve transparency. There is a large but crucial agenda to improve the monitoring of subnational budgetary and debt developments so as to improve the transparency and quality of fiscal policy at the general government level.